PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA UMKM DAERAH ISTIMEWA YOGYAKARTA - Agung Slamet Prasetyo; Lilik Ambarwati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This research is entitled the Influence of Accounting Information Systems on the Performance of MSMEs in the Special Region of Yogyakarta. This research is conducted to determine and analyze the Influence of the application of accounting information systems on the measurement of the performance of MSMEs in the Special Region of Yogyakarta. There are 70 samples taken by applying the purposive sampling method, which includes the criteria for MSMEs that apply accounting information systems and specifically focus on culinary, fashion and craft sectors. Data are collected by using a questionnaire that has been tested for its validity and reliability, and then distributed to the respondents. The results of this study indicate that the accounting information system variable has a significant positive effect on the performance of MSMEs in the Special Region of Yogyakarta. The results of the analysis reveal that the regression coefficient value is 0.532, showing that the accounting information system has a positive influence on the performance of MSMEs, meaning that the better use of accounting information systems at MSMEs results in the better performance of MSMEs in the Special Region of Yogyakarta. The accounting information system has an influence on the performance of MSMEs in the Special Region of Yogyakarta as much as 43.5% and the remaining 56.5% is a contribution from other variables which are not included in this study.